The Message of Islam is Civilizational Integration, not Civilizational Clash - A New Rebuttal of Huntington’s Theory (The International Journal for Scientific Research, 2023)
There are some debates occasionally for dialogue and rapprochement to close the human societies of different religions and ethnicities, especially between the West and Islam, but there are some obstructions thwart these attempts.This paper has several questions in this track, and it focuses on the criticism of Huntington's theory in a new way. This paper also addresses the views of Muslim scholars compared to Westerners on the issue of conflict and its reality, and Islam`s innocence from what has been attributed to its hostility to other nations, especially the Western world, which links it to the Islamic world, has historical positions, and other economic and political positions that have been renewed in the past and the current century.
Keywords: Dialogue; Conflict; Huntington; Islam; Western World